Abstracts Accepted for Presentation at Orthopaedic Trauma or Arthroplasty Conferences: Which Conference Is the Best Indicator of Future Publication?. (August 2019) - Potter, Eric; Fernandez, Isaac; Fillinger, Meghan; Potter, Dana; Nguyen, Mai P.; Reich, Michael S.
Abstract : Introduction: Time and financial resources pose limitations to orthopaedic surgeons wishing to advance their orthopaedic knowledge, and surgeons frequently must choose one meeting to attend. We sought to determine whether abstracts presented at the American Academy of Orthopaedic Surgeons (AAOS) annual meeting or the trauma (Orthopaedic Trauma Association [OTA]) or arthroplasty (American Association of Hip and Knee Surgeons [AAHKS]) subspecialty meetings, respectively, were higher yield with respect to material ultimately being published. We hypothesized that papers accepted by AAOS would demonstrate higher conversion to publication compared with OTA and AAHKS but expected abstract publication rates from OTA and AAHKS to be similar. Methods: All clinical and preclinical abstracts from the trauma and total joint arthroplasty subspecialties presented at the AAOS, OTA, and AAHKS annual meetings in 2015 were evaluated. Data collected included the current status of the publication, journal and publication date, time to publication, and country of origin (United States or international). Results: There were 516 (N = 213, AAOS; N = 303, OTA) trauma and 711 (N = 470, AAOS; N = 241 AAHKS) arthroplasty poster and podium presentations. When comparing publication rates in trauma, no significant difference was observed in overall publication rates between AAOS and OTA at 57.2% (N = 122 published) and 60.4% (N = 183 published), respectively ( P = 0.54). In addition, no significant difference was observed in overall publication rates in arthroplasty between AAOS and AAHKS, with publication rates of 65.3% (N = 307 published) and 59.8% (N = 144 published), respectively ( P = 0.17). Of abstracts that were published, AAHKS arthroplasty abstracts were more likely to be published in The Journal of Arthroplasty (JOA, 69.4%) compared with OTA trauma abstracts published in the Journal of Orthopaedic Trauma (JOT, 33.3%), P < 0.001. Conclusion: The overall publication rates, along with publication rates to premiere subspecialty journals, is indicative of forefront research being presented at the three annual meetings. Given the comparable research quality of OTA and AAHKS abstracts, the AAOS meeting appears to provide the highest yield for surgeons with more generalized practices or practices spanning multiple subspecialties.